MENYIKAPI GLOBALISASI HUKUM TANAH DENGAN KEARIFAN LOKAL - Rina Rohayu Harun (Universitas Muhammadiyah Mataram, 2019)
Land given to and owned by people with rights provided by the UUPA is to be used and utilized. The granting and possession of land with these rights will not be meaningful if its use is limited to land as the surface of the earth. The land also has a significant role in the dynamics of development. According to the 1945 Constitution of the Republic of Indonesia NRI,